Planarian Body-Wall Muscle: Regeneration and Function beyond a Simple Skeletal Support - Cebrià, Francesc (Frontiers in Cell and Developmental Biology, 2016)
The body-wall musculature of adult planarians consists of intricately organized muscle fibers, which after amputation are regenerated rapidly and with great precision through the proliferation and differentiation of pluripotent stem cells. These traits make the planarian body-wall musculature a potentially useful model for the study of cell proliferation, differentiation, and pattern formation. Planarian body-wall muscle shows some ambiguous features common to both skeletal and smooth muscle cells. However, its skeletal nature is implied by the expression of skeletal myosin heavy-chain genes and the myogenic transcription factor myoD. Where and when planarian stem cells become committed to the myogenic lineage during regeneration, how the new muscle cells are integrated into the pre-existing muscle net, and the identity of the molecular pathway controlling the myogenic gene program are key aspects of planarian muscle regeneration that need to be addressed. Expression of the conserved transcription factor myoD has been recently demonstrated in putative myogenic progenitors. Moreover, recent studies suggest that differentiated muscle cells may provide positional information to planarian stem cells during regeneration. Here, I review the limited available knowledge on planarian muscle regeneration.